1973
DOI: 10.1002/app.1973.070170720
|View full text |Cite
|
Sign up to set email alerts
|

A method for determining the optimum peroxide‐to‐amine ratio for self‐curing resins

Abstract: SynopsisThe rate of polymerization of a methacrylate monomer was influenced by the molar ratio of benzoyl peroxide to an aromatic tertiary amine accelerator when the product of the concentrations of these was kept constant. The maximum rate, measured as the minimum gel time, occurred in monomer solutions containing about 1.5 moles of peroxide per mole of amine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Because the molecule is ion exchanged onto the clay surface, the amount of acceleration within the gallery is dependent upon the charge density of the clay and the amount of clay added to the system. The optimal ratio of BPO to amine was determined to be approximately 2:1 wt% by the method of Bowen et al, by reaction of MMA with free RCS and DMA [29]. As deliberate variations in the amount of RCS added to the system were necessary, due to the addition of different types and/or amounts of RCSmodified clay, the optimal ratio of 2:1 wt% was kept constant throughout all the experiments by varying the concentration of BPO added.…”
Section: The Architecture Of Rcsmentioning
confidence: 99%
“…Because the molecule is ion exchanged onto the clay surface, the amount of acceleration within the gallery is dependent upon the charge density of the clay and the amount of clay added to the system. The optimal ratio of BPO to amine was determined to be approximately 2:1 wt% by the method of Bowen et al, by reaction of MMA with free RCS and DMA [29]. As deliberate variations in the amount of RCS added to the system were necessary, due to the addition of different types and/or amounts of RCSmodified clay, the optimal ratio of 2:1 wt% was kept constant throughout all the experiments by varying the concentration of BPO added.…”
Section: The Architecture Of Rcsmentioning
confidence: 99%
“…With low amine concentration, nearly colorless restorations, having good color stability, were obtained. [14] Also, recent studies on experimental dental acrylic composites showed that a much larger molar excess of BPO is required (about 6.5) in order to obtain the fastest cure. [9,11] Fritsch reported that bone cements prepared with DMPOH, showed increased static mechanical properties and fatigue strength, compared with those prepared with DMT.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of adding MMA monomer to Ortho-plast® resin is to extend working time by diluting accelerator (e.g., DMPT). Only the optimum molar ratio of BPO to amine provides polymerization with the minimum time [8]. This specific ratio more or less leads to reduced polymerization rate.…”
Section: Discussionmentioning
confidence: 99%